Mrs. Mary Robinson at Hunger, Nutrition, Climate Justice 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Mrs. Mary Robinson, former President of Ireland and President of the Mary Robinson Foundation, speaks at the Hunger, Nutrition, Climate Justice conference, on the 16th of April, 2013. https://ccafs.cgiar.org/events/15/apr/2013/dublin-conference-hunger-nutrition-and-climate-justice Credit for this video belongs to the Irish Presidency EU2013 The video source is Irish Aid, more videos from the conference are available at: http://eu2013.ie Find more information about the CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) at: https://ccafs.cgiar.org/